2022
DOI: 10.1155/2022/8950600
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Algorithm in Classification and Recognition of Primary Hepatic Carcinoma Images under Magnetic Resonance Imaging

Abstract: This study aimed to discuss the application value of the bias field correction algorithm in magnetic resonance imaging (MRI) images of patients with primary hepatic carcinoma (PHC). In total, 52 patients with PHC were selected as the experimental group and divided into three subgroups: mild (15 cases), moderate (19 cases), and severe (18 cases) according to pathological grading. Another 52 patients with hepatic nodules in the same period were included in the control group. All the patients underwent dynamic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…He et al, demonstrated a notable improvement in the accuracy of diagnosing primary hepatic cancer (PHC) in patients by employing a bias field correction algorithm in MRI images. This underscores the promising capability of AI algorithms in enhancing the diagnosis and prognostic evaluation of MRI scans [29]. In another study, Zeng et al, illustrated that the AI model accurately estimated the expression of ABRS from histological slides, and this estimation correlated with increased progression-free survival in patients treated with atezolizumab-bevacizumab [30].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…He et al, demonstrated a notable improvement in the accuracy of diagnosing primary hepatic cancer (PHC) in patients by employing a bias field correction algorithm in MRI images. This underscores the promising capability of AI algorithms in enhancing the diagnosis and prognostic evaluation of MRI scans [29]. In another study, Zeng et al, illustrated that the AI model accurately estimated the expression of ABRS from histological slides, and this estimation correlated with increased progression-free survival in patients treated with atezolizumab-bevacizumab [30].…”
Section: Resultsmentioning
confidence: 97%
“…In a study, researchers refined the diagnosis of primary hepatic cancer (PHC) by applying bias field modification to magnetic resonance imaging. The study revealed that artificial intelligence enhances the accuracy of imaging diagnosis [29]. Another study assessed the responsiveness of hepatocellular carcinoma (HCC) patients to atezolizumab-bevacizumab treatment, employing an artificial intelligence (AI) pathology model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is currently employed in nearly all sub-branches of medicine, including diagnosis, treatment, drug development technology, and even improving the doctor–patient interaction. 3 - 7 Artificial intelligence is also being utilized to improve medical education. 8…”
Section: Introductionmentioning
confidence: 99%